Exploration of Barriers of Small Industry Local Content Certification - Abadi, Indera Sufi; Arviansyah , Arviansyah (Syntax Corporation, 2025)
Micro and Small Enterprises (MSEs) play a crucial role in strengthening the national economy, yet only a fraction of MSEs participated to comply with local content certification requirements. The ministry of industry with Sistem Informasi Industri Nasional (SIINAS) platform is designed to facilitate this certification process for free, but MSE participation remains small when compared to the total number of MSE in Indonesia. Some businesses actively adopt it, while others face challenges that dettering their engagement. Understanding the factors influencing MSE's decisions to participate in local content certification using SIINAS is critical for enhancing adoption rates and improving policy effectiveness. This study employs a qualitative research approach using the thematic analysis to analyze emerging themes from MSEs’ experiences. By applying Thematic Analysis methodology, data from MSE participants was examined to uncover the barriers and drivers affecting SIINAS adoption. The findings align with Innovation Resistance Theory (IRT). This study contributes to the theoretical understanding of MSE participation in digital certification and offers practical recommendations for enhancing SIINAS adoption through more efficient and effective system improvements and also targeted support strategies. Strengthening MSE engagement in local content certification can ultimately drive broader industrial compliance and economic growth.